"Patients Are Not Following the [Adherence] Club Rules Anymore": A Realist Case Study of the Antiretroviral Treatment Adherence Club, South Africa. (October 2018) - Mukumbang, Ferdinand C.; Marchal, Bruno; Van Belle, Sara; van Wyk, Brian
There is growing evidence that differentiated care models employed to manage treatment-experienced patients on antiretroviral therapy could improve adherence to medication and retention in care. We conducted a realist evaluation to determine how, why, for whom, and under what health system context the adherence club intervention works (or not) in real-life implementation. In the first phase, we developed an initial program theory of the adherence club intervention. In this study, we report on an explanatory theory-testing case study to test the initial theory. We conducted a retrospective cohort analysis and an explanatory qualitative study to gain insights into the important mechanisms activated by the adherence club intervention and the relevant context conditions that trigger the different mechanisms to achieve the observed outcomes. This study identified potential mitigating circumstances under which the adherence club program could be implemented, which could inform the rollout and implementation of the adherence club intervention.